The PKM-based Improving Demersal and Small Pelagic Fish Processing Income in Kosong Island Jayapura City : Peningkatan Pendapatan Pengolahan Ikan Demersal dan Ikan Pelagis Kecil berbasis PKM di Pulau Kosong Kota Jayapura - Daniel ZK. Wambrauw; Lolita Tuhumena; Vita Purnamasari; Fabianus Batlayeri; Alpredo Diaz Agapi L.; Nicea Roona Paranoan (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2024)
The partner group, consisting of fishermen's wives in Pulau Kosong, Jayapura City, often assists their husbands, who work as gillnet fishermen, by preserving excess catches. Fish preservation is done by sun-drying the fish on wooden bridges in an open environment, producing dried fish products. However, the group faces challenges, including a lack of skills in hygienic fish processing and limited knowledge of financial management and marketing. This community service program involved socialization and training aimed at increasing the income of demersal and pelagic fish processors. The program employed the Participatory Rural Appraisal (PRA) method as the applied solution approach. Activities began with a location survey, followed by training on proper and hygienic packaging techniques and simple bookkeeping. Pre-tests and post-tests were conducted for the partners, with results analyzed using the normality gain test to assess the effectiveness of the intervention. Based on the N-Gain Score calculation, a score of 70.83 was obtained, categorized as moderately effective, indicating a significant improvement in the knowledge of fishermen's wives regarding the training materials.